Extracorporeal photopheresis reduces the T cell stimulatory capacity of human primary blood conventional dendritic cells type 1 - Heger, Lukas; Berking, Carola; Hackstein, Holger (Frontiers in Immunology, 2025)
IntroductionExtracorporeal photopheresis (ECP) is an immunomodulatory treatment option for different T cell-mediated diseases such as cutaneous T cell lymphoma (CTCL) and chronic graft-versus-host disease (GvHD). While in CTCL the polarization of T cells is shifted towards T helper cells type 1 (TH1) and an immune response against the lymphoma is induced, ECP in GvHD rather leads to the expansion of regulatory T cells (Treg). How ECP regulates the immune response dependent on the underlying disease is still not exactly known. As dendritic cells (DCs) are crucial regulators of the immune response, it is supposed that they are key players in the immunomodulatory effects of ECP. However, due to the scarcity of primary DCs in blood, research has focused on in vitro-generated monocyte-derived DCs so far.MethodsHere, we present for the first time how the primary human blood DC subpopulations, i.e., conventional DCs type 1 (cDC1), cDC2, DC3, and plasmacytoid DCs (pDC), directly isolated from blood of healthy donors, respond to in vitro ECP treatment. ResultsWe demonstrate that the exposure to 8-methoxypsoralen and UV-A light irradiation induces apoptosis in Toll-like receptor ligand-activated cDC1 and pDC as well as - to a minor extent - in steady state cDC1, cDC2, and DC3. However, the selective effect of ECP on viability of DC subpopulations was dependent on culture duration (18h vs. 42h) as well as condition (steady state vs. TLR ligand activated). Further, ECP modulates the expression of the co-stimulatory and co-regulatory molecules CD40, CD86, and PD-L1 on DC subpopulations. While ECP did not affect the T cell stimulatory capacity of cDC2 and DC3, ECP-treated cDC1 and - to a minor extent - pDC showed reduced activation of memory T cells and diminished secretion of TH1- and TH17-associated cytokines. ConclusionThus, especially blood cDC1 are direct targets of ECP and the reduction of their T cell stimulatory capacity might contribute to the clinical efficacy observed in chronic GvHD patients.